Effect of educational intervention on knowledge regarding emergency contraception among girls of higher secondary school. - Sapkota, Devi Kumari (2011)
ABSTRACT: This study entitled "Effect of Educational Intervention on Knowledge Regarding Emergency Contraception among Girls of Higher Secondary School" was carried out in two colleges: Balkumari College Narayangarh and Saptagandaki College Bharatpur of Chitwan district. The main objective of the study was to find out the effectiveness of educational intervention on knowledge regarding emergency contraception (EC) among girl students of Higher Secondary School. A quasi experimental research design: pretest and posttest non-equivalent group was used in the study and two colleges were used as one for experimental group and other for control group. The population of the study was girl students of Higher Secondary School. Forty-five students were selected from each college by using non-probability purposive sampling technique. The semi structural self administered questionnaire was used for data collection. The educational package was administered to the experimental group on the next day of pretest, and posttest was done with same instrument after one week of pretest. In control group, pretest and posttest were taken using same instrument without intervention. For data analysis, descriptive and inferential statistics were used. The paired-sample "t" test was computed to find out the differences between pretest and posttest mean knowledge scores of the experimental and control group at the 0.05 level of significance. In the comparison of grand mean knowledge scores between pretest and posttest between the group, significant difference was found in experimental group, p value was 0.000 and the difference was not significant in control group, the P value was 0.668 (>0.05). The "f" value was also calculated at the 0.01 level of significance to find out the homogeneity of variance, only little different was found in pretest but in posttest it was found significant (f value was more than tabulated value: 4.905). The gained mean knowledge score of respondents in experimental group was 9.91 while in control group it was 0.58. The result of the study showed that, the educational intervention for the girl students significantly increased the knowledge about EC. The study has supported the hypothesis: there is significant increase in knowledge score in experimental group than control group after educational intervention.